An invisible workforce: the neglected role of cleaners in patient safety on maternity units. Issue 1 (1st January 2019) - Cross, Suzanne; Gon, Giorgia; Morrison, Emma; Afsana, Koasar; Ali, Said M.; Manjang, Tina; Manneh, Lamin; Rahman, Atiya; Saxena, Deepak; Vora, Kranti; Graham, Wendy J.
ABSTRACT: Hospital cleaning has been shown to impact on rates of healthcare-associated infections (HCAIs) and good environmental hygiene is critical to quality care, yet those tasked with the role of ensuring a safe and clean environment often go unrecognised as members of the healthcare workforce. Sepsis is a leading cause of maternal and newborn death, a significant proportion of these cases are estimated to be due to HCAIs. Deliveries in health institutions have now reached 75% globally, and in low and middle income countries the corresponding increased pressure on facilities has impacted both quality of care provided and quality of the birth environment in terms of infection prevention and control (IPC) and HCAIs. The paper discusses the neglected role of health facility cleaners, providing evidence from the literature and from needs assessments conducted by The Soapbox Collaborative and partners in Bangladesh, India, The Gambia and Zanzibar. While not the primary focus of the assessments, common themes emerged consistently pointing to institutional neglect of cleaning and cleaners. The paper argues that low status within facilities, wider societal marginalisation, lack of training, and poor pay and working conditions contribute to the lack of prioritisation placed on health facility environmental hygiene. With increased international attention focused towards health facility water, sanitation and hygiene and a growing focus on IPC, now is the time to address the neglect of this frontline healthcare workforce. We propose that provision of and improved training can enable the recognition of the valuable role cleaning staff play, as well as equipping these staff with the tools required to perform their job to the highest standard. In addition to training, wider systems changes are necessary to establish improvements in environmental hygiene and the role of cleaning staff, including addressing resource availability, supportive supervision, and an increased emphasis on preventative healthcare.